2006
DOI: 10.1111/j.1469-0691.2006.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness between group B streptococci originating from bovine mastitis and a human group B streptococcus type V cluster displaying an identical pulsed-field gel electrophoresis pattern

Abstract: Twenty isolates of group B streptococcus (GBS) were recovered from the milk of cows with bovine mastitis on three farms located in the south and south-east of Brazil between 1987 and 1988. These isolates were characterised by molecular methods and compared with a collection of 103 human GBS isolates from colonised and infected patients in the same region between 1980 and 2003. Some of the bovine isolates shared identical or similar pulsed-field gel electrophoresis (PFGE) patterns with a PFGE clone of human GBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 39 publications
(66 reference statements)
1
35
0
1
Order By: Relevance
“…This study, along with previous studies, indicates that these serotype V GBS are clonal and are from CC 1 (4,5,15,16,23). While colonizing serotype V strains in this study were also occasionally found in a variety of other lineages, the only other invasive serotype V strain in this study was ST-26, an ST related to a bovine serotype V ST-256 strain isolated from a bovine udder in Brazil (27). CC 1 is comprised of the smallest number of STs of the major CCs associated with invasive disease in this study, with 93% of the CC 1 strains having a single ST (ST-1), suggesting that the diversity of STs within a CC may reflect how recently an invasive clone arose in the human population.…”
Section: Discussionsupporting
confidence: 78%
“…This study, along with previous studies, indicates that these serotype V GBS are clonal and are from CC 1 (4,5,15,16,23). While colonizing serotype V strains in this study were also occasionally found in a variety of other lineages, the only other invasive serotype V strain in this study was ST-26, an ST related to a bovine serotype V ST-256 strain isolated from a bovine udder in Brazil (27). CC 1 is comprised of the smallest number of STs of the major CCs associated with invasive disease in this study, with 93% of the CC 1 strains having a single ST (ST-1), suggesting that the diversity of STs within a CC may reflect how recently an invasive clone arose in the human population.…”
Section: Discussionsupporting
confidence: 78%
“…Gels were stained with ethidium bromide and photographed under UV light. Criteria for analysis of the PFGE patterns were those originally suggested by Tenover et al (1995) and used in our previous studies (Oliveira et al 2005(Oliveira et al , 2006. PCR -DNA extraction was performed according to Sambrook et al (1989).…”
Section: Methodsmentioning
confidence: 99%
“…Ideally, assessment of the potential for interspecies transmission is based on the analysis of contemporaneous, sympatric isolates. With 1 exception ( 13 ), however, most comparative studies were not based on isolates from the same geographic region and the same period, or, if they were, they covered a very limited number of S. agalactiae– positive farms or animals ( 14 , 15 ). Our aim with this study was to provide insight into the hazard of interspecies transmission of S. agalactiae by comparing contemporaneous populations of S. agalactiae from humans and dairy cattle in Finland and Sweden.…”
mentioning
confidence: 99%